Reproductive parameters in Beira Baixa Merino ewes - Rodrigues, J.P.V. (2011)
A collection and selection of data has been carried on the Merino Beira Baixa ewes at Escola Superior Agraria (Agricultural School) in Castelo Branco (ESACB) in Portugal from 1981 to 1989. According to the birth type of females (single or double) their average age at the time of first lambing amounted to 599.85±150.47 days and to 574.13±147.06 days. Diferences were not significant. However this parameter was influenced by the “year” factor (P<0.01) Is was shown that lambing interval (IP) did not depended on parturition months inside the season but depended on parturition months between the parturition season (from january to april 322.66±79.31 days and from august to december 380.67±73.81 days). The IP revealed significant diferences (P<0.01) in terms of ewe age at lambing. The apparent fertility rate, ptolificacy rate and numerical productivity are, in 1981-87 and 1987-88, 86,6% vs 85,9%, 114, 2% vs 112,3%, 92,7% vs 84,9% respectively. All these rates were influenced by the ewes age at lambing. Reproductive parameters in period with altered reproductive management (two autonomous herds without ewes transference) are diferentes, favourable to Autumn mating season. Analysis was carried on further reproductive parameters.